Lettuce production in protected area - Nino Rotim (Glasnik Zaštite Bilja, 2021)
Lettuce is a vegetable crop that is traditionally grown in protected aera during autumn and winter in Herzegovina. Short vegetation period and the fact that it is a good pre-culture of leading vegetable crops gives it an advantage over other vegetable species. In addition to the modest biological requirements for its successful growth and development inside it is necessary to ensure sufficient light, intensity and optimal temperature. Head lettuce is suitable for production in a greenhouses and hothouses (Lactuca saviva var. capitata) in which we distinguish types with crispy leaves (Iceberg lettuce) and types with butter leaves (Butterhead lettuce). Salad harvisting takes place on several occasions when the heads reach a certain shape, size and firmness.